Rehabilitation and Development of Heritage Villages in the Province of Almandaq - Baha Area: (Almashaya'a Village as a Case Study) - Alhiagi, Yasser Hashem Emad (Jordan Journal for History and Archaeology, 2021)
Saudi Arabia has a rich architectural heritage reflecting its historical memory dating back centuries. The variety of villages throughout the kingdom are a unique sphere for social, economic and architectural interactions. Despite the attention given to the architectural heritage by the General Commission for Tourism and National Heritage, as a national interest, there are heritage villages still suffering from multiple problems such as desertion, deterioration as a result of natural and human factors which effect massively the economic, social and architectural aspects. This study utilizes descriptive and analytical methodology to investigate the restoration and revitalization of the residential buildings in the Almashaya'a village and presents a plan for rehabilitation to preserve the buildings in an attractive and sustainable environment for activities, events and handicrafts that reveals its heritage and architectural value